Notices (Blackfriars, 1933)
Florilegium Patristicum, Fasciculus XXXVI: S. Alberti Magni Quaestiones de bono (Summa de bono, q. 1—10). Nunc primum edidit prolegomenis apparatu critico notis instruxit Henricus Kühle. (Hanstein, Bonn; 53 pp.; 2.50 mks.) St. Anselm. A Critical Biography. By Joseph Clayton, F.R.Hist.S. (Bruce Publishing Co.; $1.75.) Life of Fr. Ignatius Spencer, C.P. By Urban Young, C.P. (Burns, Oates & Washbourne; pp. viii, 286; 6/-). The Pilgrim's Guide to Rome. By Capt. C. C. Constable. (Burns, Oates & Washbourne; pp. 163; 4/6). The Beggar and, Other Stories. By Douglas Newton. (Washbourne & Bogan, London; pp. 286; 7/6). Chimes from Leighton's Church Tower. By the Rev. Kenneth Knight Hallowes. (Methuen; 5/-). Town to Country. By G. C. Heseltine. (Burns, Oates & Washbourne, Ltd.; 1/6).